Relationship between violence and social integration in classrooms of elementary education (2010)
The aggressiveness in the school classrooms is a growing up phenomenon that is now in the center of the social concern. This study was conducted in a Elementary School Center at The Principality of Asturias, and aims to establish the relationship between the interactions the children make with their peers and the violent behaviors inside of the school based on the age and gender. Participants were 132 students. The results support the idea that boys show more violent behavior than girls, the age issue was significant (the upper grade of the student means more use of the violence). Besides the kids seen by their teacher as violent are rejected and less popular in the class; this does not happen in the case of both girls and the children of the lower grades, because there is not a significant correlation between aggressiveness and integration into the group